Infiltration Capacity in 4 Land Use Types in the Sei Silau Barat village, Setia Janji sub-district, district of Asahan - Siti Maqdisa; jamilah Jamilah; purba marpaung (Jurnal Agroekoteknologi, 2018)
ABSTRACT The objective of this research was to know the infiltration capacity in 4 land use types in the Sei Silau Barat village, Setia Janji sub-district, district of Asahan. Coordinate on settlement area of 99o29’40” N 2o56’24” E and 99o29’50” N dan 2o56’18” E, on corps of palawija at coordinate of 99o31’10” N 2o56’56” E and 99o30’50” N 2o56’38” E, at oil palm estate at coordinate of 99o30’30” N 2o57’16” E and 99o30’20” N 2o56’52” E, and at rubber estate at coordinate of 99o30’20” N 2o56’52” E and 99o30’10” N 2o55’58” E. Soil analysis results at settlement area its texture was sandy clay, organic matter content was 0,54%, rate of water was 30,61%, bulk density was             1,05 g/cm3, particle density was 2,19 g/cm3, and porosity was 51,81% with infiltration capacity was 7,8 x 10-6 m/s (medium). At corps of palawija, its texture was sandy clay loam, organic matter content was 1,68%, rate of water was 50,52%, bulk density was 1,01 g/cm3, particle density was 2,04 g/cm3, and porosity was 50% with infiltration capacity  was 37 x 10-6 m/s (quickly). At palm oil estate, its texture was sandy clay loam, organic matter content was 0,84%, rate of water was 27,69%, bulk density was 1,14 g/cm3, particle density was 2,28 g/cm3, and porosity was 49,09% with infiltration capacity was 8,4 x 10-6 m/s (medium). And at rubber estate, its texture was sandy clay loam, organic matter content was 1,14%, rate of water was 38,71%, bulk density was 1,1 g/cm3, particle density was 2,24 g/cm3, and porosity was 50,91% with infiltration capacity was 0,6 x 10-6 m/s (very slow).   Keywords: Infiltration capacity, land use types, Sei Silau Barat Village